Amino acid analysis of lipases from oil pollutant isolates: Cunninghamella verticillata and geotrichum candidum - Gopinath, Subash Chandra Bose; Anbu, Periasamy; Md Arshad, Mohd Khairuddin; Lakshmipriya, Thangavel; Voon, Chun Hong; Hashim, Uda; Al-Douri, Yarub; Citartan, Marimuthu; Tang, Thean-Hock; Chen, Yeng (Prince of Songkla University, 2018)
Lipase is an enzyme commonly used in food, dairy, and other industries. Fungal lipases are more commonly used due to their secretion and easier production. Analyses of the amino acid composition of microbial lipases will hasten their potential usage in industrial applications. In this study, the major amino acid compositions of lipases secreted by oil pollutant isolates (Cunninghamella verticillata and Geotrichum candidum) enriched with fatty substances were analyzed by high performance liquid chromatography. Among eight major amino acids found in these lipases, histidine and ornithine were predominant. Lysine was absent from lipase generated by C. verticillata, while glutamine was absent from that produced by G. candidum. Conversely, glutamic acid, asparagine, histidine and arginine were present in slightly higher amounts in G. candidum. However, a slight decrease in aspartic acid and ornithine was observed in G. candidum. Analyses of the amino acids composition of lipase can potentially facilitate to predict the nature of this enzyme.